Use of temperature-sensitive mutants to study gene expression during sporulation in Bacillus subtilis. - Young, M (1976)
Two temperature-sensitive sporulation mutants have been characterized. One mutant, which is blocked at stage II, has a short temperature-sensitive period that occurs at about the time when the spore septum is formed. Cells can escape the sporulation block, if incubated for a short period at the permissive temperature, but are prevented from doing so by inhibitors of transcription and translation; this suggests that the product of the defective gene is a protein and that the messenger ribonucleic acid which codes for this protein is short-lived. The other mutant is blocked at stage IV to V and has a long temperature-sensitive period that starts during stage III and precedes the stage at which the mutational defect is phenotypically expressed. The behavior of this mutant in temperature-shift experiments suggests that synthesis of the product of the defective gene commences long before it assumes its physiological function.